Analisis Dampak Bisnis Rumah Sewa Selama Pandemi Covid-19 - Trans Ningsih; Suginam Suginam (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Managing a rental house business is a best profitable business opportunity, conditions changed during the Covid-19 pandemic which was also affected by the pandemic. This study aims to analyze the impact rental house business during the Covid-19 pandemic at Pasar Baru Padang Bulan, Medan. This research method uses quantitative descriptive analysis. Involving a sample of 43 people from 2 types of rental house categories. Data collection was carried out on respondents who continued to rent houses during the period May 2020 - February 2021. Aspects of business discussion were aspects of needs, aspects of costs and facilities, aspects of marketing, and aspects of economic. Based on research results, the house rental business in Pasar Baru Padang Bulan area, Medan has experienced a decline in income as a result of a decrease in the number of consumen, but the need for a place to live remains the most common reason for consumen to stay in rental house because they have to keep working during the pandemic. When viewed from the aspect of costs and facilities, rented houses with standard facilities experienced a significant decline in consumen both in the first period and the end of 2020 and resulted in a decrease in income of up to 88%. Meanwhile, for rental houses that have complete facilities, the number of consumen in the first period decreased by up to 50%. The New Normal regulations implemented by the Medan city government and the many businesses that have resumed operations are one of the reasons rental houses are able to revive. The rental house in Padang Bulan area has fulfilled all four marketing criteria, the difference in the utility form where the facilities offered by the rental house are different. So that the final decision is in the hands of the consumen to choose.